The Role of DSN-MUI Fatwa No.153/DSN-MUI/VI/2022 in Realizing Consumer Protection in The Islamic Banking Sector - Anas, Irham; Alfarouq , A.R. Zulfikar; Nasution, Atiqoh (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
Murabahah financing, a sale-based model, is one of the key instruments in Islamic banking but faces challenges in Indonesia. One major issue is early repayment, where customers struggle to secure fair discounts, causing dissatisfaction and debates. To address this, the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) issued Fatwa No. 153/DSN-MUI/VI/2022, mandating Islamic banks to provide early repayment discounts as a compulsory provision rather than a discretionary policy. This study aims to analyze the implications of the fatwa on Murabahah financing and identify strategies for its implementation in Islamic banking. A qualitative research method was employed, involving content analysis of the fatwa, Islamic banking regulations, and expert interviews. The results reveal that the fatwa provides legal clarity, ensuring discounts are obligatory, thereby addressing customers’ concerns and fostering fairness. Additionally, the study highlights key strategies, such as integrating discount calculation mechanisms in financing agreements, revising operational guidelines, applying historical cost criteria for determining ta’widh fees and adjustment of the calculation formula of PU-PMSJT in the financing product guidelines for Murabahah in Islamic banking. These measures promote mutual benefits for customers and banks, enhancing trust and sustainability in the Islamic finance ecosystem.   Pembiayaan Murabahah, sebagai model berbasis jual beli, merupakan salah satu instrumen utama dalam perbankan syariah, namun menghadapi tantangan di Indonesia. Salah satu masalah utama adalah pelunasan dipercepat, di mana nasabah kesulitan mendapatkan potongan pelunasan yang adil, sehingga menimbulkan ketidakpuasan dan perdebatan. Untuk mengatasi masalah ini, Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) mengeluarkan Fatwa No. 153/DSN-MUI/VI/2022 yang mewajibkan bank syariah memberikan potongan pelunasan dipercepat sebagai ketentuan wajib, bukan kebijakan diskresi. Penelitian ini bertujuan untuk menganalisis implikasi fatwa tersebut terhadap pembiayaan Murabahah dan mengidentifikasi strategi penerapannya dalam perbankan syariah. Metode penelitian kualitatif digunakan, meliputi analisis konten terhadap dokumen fatwa, regulasi perbankan syariah, dan wawancara dengan para ahli. Hasil penelitian menunjukkan bahwa fatwa ini memberikan kejelasan hukum, memastikan potongan pelunasan menjadi kewajiban, sehingga menjawab kekhawatiran nasabah dan meningkatkan keadilan. Selain itu, penelitian ini menyoroti strategi utama seperti mengintegrasikan mekanisme perhitungan potongan pelunasan dalam perjanjian pembiayaan, merevisi pedoman operasional, menerapkan kriteria biaya historis untuk menentukan ta’widh atas pelunasan dipercepat dan penyesuaian formula perhitunganPU-PMSJT pada buku pedoman produk pembiayaan murabahah perbankan syariah. Langkah-langkah ini mendorong manfaat bersama bagi nasabah dan bank, sekaligus memperkuat kepercayaan dan keberlanjutan dalam ekosistem keuangan syariah.